Agus Sunyoto’s Thoughts on the Uniqueness of Nusantara Islamic Education: An Analysis of PRAMISTARA - Rahmah, Farida Novita; Saiful Umam (Journal of Islamic Civilization, 2025)
This article examines Agus Sunyoto’s ideas on the distinctiveness of Nusantara Islamic education as articulated through the Pramistara (Pesantren Ramadhan Islam Nusantara) program, which emerges as a response to the challenges of globalization and the Industrial Revolution 4.0. Employing a descriptive qualitative approach through literature review and narrative analysis of Pramistara’s texts, lectures, and documents, this study applies Michel Foucault’s archaeology of knowledge to trace how Sunyoto constructs the discourse of Nusantara Islam across historical, epistemological, and power-related layers that legitimize Pramistara as a continuation of the archipelagic Islamic tradition. In addition, Paulo Freire’s critical pedagogy is used to examine how Pramistara’s educational practices foster dialogical learning, critical consciousness, and socio-spiritual awareness in addressing contemporary issues. The findings indicate that Pramistara is not merely a Ramadan study forum, but a strategic educational space that integrates pesantren traditions, Indonesian historical narratives, Sufism, and global issues such as geopolitics, proxy wars, and cryptocurrency. Through this integrative approach, Agus Sunyoto positions Nusantara Islamic education as a model that balances intellectual rigor with spiritual transformation, while simultaneously reinforcing local identity in the face of global secularizing forces. Foucault’s framework elucidates the knowledge structures that underpin the discourse of Nusantara Islam, whereas Freire’s theory underscores Pramistara’s role in cultivating critical, reflective, and moderate learners. Consequently, Pramistara emerges as an alternative educational model that sustains continuity with tradition while equipping the younger generation to navigate the challenges of a disruptive era.